2015
DOI: 10.1007/s11207-015-0799-4
|View full text |Cite
|
Sign up to set email alerts
|

The Storm of Decameter Spikes During the Event of 14 June 2012

Abstract: An event on 14 June 2012, observed with the radio telescopes UTR-2 (Kharkov, Ukraine), URAN-2 (Poltava, Ukraine), and NDA (Nançay, France) during a joint Summer campaign, is analyzed and discussed. The high solar activity resulted in a storm of spikes, and a storm of Type III bursts, Type IIIb bursts, and a Type IV burst observed in the decameter band. During the observed time interval, the average flux of radio emission changed twice. Using spikes as a tool for diagnostics of plasma parameters, we followed va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 17 publications
7
28
1
Order By: Relevance
“…The duration change with frequency may carry an important information about the plasma parameters in the emission source. Recently it was shown by Shevchuk et al [2016] that the durations of solar spikes are possibly defined by the collision times in plasma and hence can be used as a plasma temperature diagnostic tool. The durations of S-bursts are several times shorter than the collision times estimated at the corresponding heights.…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration change with frequency may carry an important information about the plasma parameters in the emission source. Recently it was shown by Shevchuk et al [2016] that the durations of solar spikes are possibly defined by the collision times in plasma and hence can be used as a plasma temperature diagnostic tool. The durations of S-bursts are several times shorter than the collision times estimated at the corresponding heights.…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…Their durations are considerably less than 1 s with the shortest reported value reaching 20 ms [McConnell, 1982]. The durations of other well-known short bursts, solar spikes, vary from 0.1 to 1 s at the mentioned frequencies [Shevchuk et al, 2016]. In addition Magdalenic et al [2006] reported about the super-short structures of metric type IV bursts whose durations were as small as 4 ms. S-bursts are observed exclusively at meter and decameter wavelengths [Dorovskyy et al, 2006;Melnik et al, 2010;Morosan et al, 2015].…”
Section: Introductionmentioning
confidence: 96%
“…The part of the dynamic spectrum with storm of spikes simultaneously with storm of Type III bursts is presented on Figure 1. This storm lasted Proceedings of Eleventh Workshop "Solar Influences on the Magnetosphere, Ionosphere and Atmosphere" Primorsko, Bulgaria, June 3÷7, 2019 during all day of observations from 04:45 up to 16:00 UT [Shevchuk N. V., et al, 2016]. The dynamic spectrum was recorded with URAN-2 coupled with new receiver DSP-Z.…”
Section: Observationsmentioning
confidence: 99%
“…At times of high solar activity, decameter spikes have also been observed and shown to be the low-frequency analogues of high-frequency (GHz) solar spikes used to derive the coronal plasma parameters [Shevchuk et al, 2016].…”
Section: Propagation Of Electron Beams Through the High Coronamentioning
confidence: 99%